Accuracy of Intravenous Electrocardiography Confirmation of Peripherally Inserted Central Catheter for Parenteral Nutrition. (5th February 2016) - Mundi, Manpreet S.; Edakkanambeth Varayil, Jithinraj; McMahon, Megan T.; Okano, Akiko; Vallumsetla, Nishanth; Bonnes, Sara L.; Andrews, James C.; Hurt, Ryan T.
Abstract : Background: Parenteral nutrition (PN) is a life‐saving therapy for patients with intestinal failure. Safe delivery of hyperosmotic solution requires a central venous catheter (CVC) with tip in the lower superior vena cava (SVC) or at the SVC–right atrium (RA) junction. To reduce cost and delay in use of CVC, new techniques such as intravascular electrocardiogram (ECG) are being used for tip confirmation in place of chest x‐ray (CXR). The present study assessed for accuracy of ECG confirmation in home PN (HPN). Methods : Records for all patients consulted for HPN from December 17, 2014, to June 16, 2015, were reviewed for patient demographics, diagnosis leading to HPN initiation, and ECG and CXR confirmation. CXRs were subsequently reviewed by a radiologist to reassess location of the CVC tip and identify those that should be adjusted. Results : Seventy‐three patients were eligible, and after assessment for research authorization and postplacement CXR, 17 patients (30% male) with an age of 54 ± 14 years were reviewed. In all patients, postplacement intravascular ECG reading stated tip in the SVC. However, based on CXR, the location of the catheter tip was satisfactory (low SVC or SVC‐RA junction) in 10 of 17 patients (59%). Conclusion : Due to the high osmolality of PN, CVC tip location is of paramount importance. After radiology review of CXR, we noted that 7 of 17 (41%) peripherally inserted central catheter lines were in an unsatisfactory position despite ECG confirmation. With current data available, intravenous ECG confirmation should not be used as the sole source of tip confirmation in patients receiving HPN.